Analysis of the Use of the Hand Sign Method in Learning Angklung Music for PGSD Students at Efarina University - Tambunan, Jubelando O (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
The Kodaly Method especially the hand sign is a learning method which applies codes in the learning process. In this study, this learning method is applied to the sixth semester students of the primary education teacher program in the Efarina University. This study aims to analyse the application of Hand Sign method on the study of music education by using angklung as the musical instrument. A qualitative research method with a case study research design is applied in this study. It is to describe a phenomenon that is the object of the research, namely the hand sign method in learning music with angklung. The objects of this study are the sixth semester students of the primary education program of Efarina University with the total number 25 students. This study reveals that the application of the Hand Sign method in learning music through Angklung is more effective compared to the traditional method that is the reading notation method. It is found that through the method, the students are able to understand the notes and play music with angklung very well.